Risk Factors for the Occurrence of Benign Paroxysmal Positional Vertigo: A Systematic Review and Meta-Analysis - Chen, Jinbao; Zhao, Weisong; Yue, Xuejing; Zhang, Ping (Frontiers in Neurology, 2020)
Background and Purpose: The lifetime prevalence of benign paroxysmal positional vertigo (BPPV) is high, especially in the elderly. Patients with BPPV are more susceptible to ischemic stroke, dementia, and fractures, severely reducing quality of life of patients. Many studies have analyzed risk factors for the occurrence of BPPV. However, the results of these studies are not identical. We performed this meta-analysis to determine potential risk factors associated with the occurrence of BPPV. Methods: PubMed, EMBASE, and the Cochrane Library (January 2000 through March 2020) were systematically searched for eligible studies analyzing risk factors for the occurrence of BPPV. Reference lists of eligible studies were also reviewed. We selected observational studies in English with a control group and sufficient data. Pooled odds ratios (ORs) or the mean differences (MDs) and 95% confidence intervals (CIs) were calculated to measure the impacts of all potential risk factors. Heterogeneity among studies was evaluated using the Q-test and I2 statistics. We used the random-effect model or the fixed-effect model according to the heterogeneity among the included studies. Results: We eventually included 19 studies published between 2006 and 2019, including 2,618 patients with BPPV and 11,668 participants without BPPV in total. In this meta-analysis, the occurrence of BPPV was significantly associated with female gender (OR = 1.18; 95% CI, 1.05–1.32; P = 0.004), serum vitamin D level (MD = −2.12; 95% CI, −3.85 to −0.38; P = 0.02), osteoporosis (OR = 2.49; 95% CI, 1.39–4.46; P = 0.002), migraine (OR = 4.40; 95% CI, 2.67–7.25; P < 0.00001), head trauma (OR = 3.42; 95% CI, 1.21–9.70; P = 0.02), and total cholesterol level (MD = 0.32; 95% CI, 0.02–0.62; P = 0.03). Conclusion: Female gender, vitamin D deficiency, osteoporosis, migraine, head trauma, and high TC level were risk factors for the occurrence of BPPV. However, the effects of other risk factors on BPPV occurrence need further investigations.